Brain protection in cardiac surgery - Bonser, Robert S.; Pagano, Domenico; Haverich, A. 1953- (Axel) (Monographs in cardiac surgery., 2011)
This book is part of the "Monographs in Cardiac Surgery Series"--Introducing 'basic science into the cardiac operating room'. It offers fast systematic review of small areas of cardiac surgery including up-to-date information. This will allow more rapid publication than the alternative cardiac surgery 'tomes'. This entry into the series will provide readers with a complete review of the current understanding in brain injury and the methods used to avoid or limit its effects on patient morbidity and mortality.